Hubungan Antara Screen Based Activity dengan Ketajaman Penglihatan Anak Usia Sekolah - Wahyuningrum, Eka; Ina, Apolonia Antonilda; Marlinda, Endah (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2021)
Screen based activity in school children cannot be avoided. One physical effect is a decrease in visual acuity.Some studies suggest there is a relationship between screen time and decreased visual acuity, while other studiessuggest different things. The purpose of this study was to determine the relationship between screens basedactivity and visual acuity of school age children. The research method uses a prospective cohort with totalsampling as a sample selection method, bivariate analysis is performed with a chi-square test and 95% confidencelevel. The results found that most respondents were male (58.3%), using TV (88.2%) and mobile phones (83.4%)as a screen based activity media, playing online games (46.7%) and decreased vision of the right eye (30%) andthe left eye (43.3%). Bivariate analysis shows that there is a significant relationship between screen based activityand the child's right eye vision (p-value <0.001) and the child's left eye vision (p-value <0.001). The conclusionis that there is a significant relationship between screen-based activity and the visual acuity of school-agedchildren.